Electroconductive PEDOT nanoparticle integrated scaffolds for spinal cord tissue repair - Serafin, A. (2022)
Background: Hostile environment around the lesion site following spinal cord injury (SCI) prevents the re-establishment of neuronal tracks, thus significantly limiting the regenerative capability. Electroconductive scaffolds are emerging as a promising option for SCI repair, though currently available conductive polymers such as polymer poly(3,4-ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS) present poor biofunctionality and biocompatibility, thus limiting their effective use in SCI tissue engineering (TE) treatment strategies. Methods: PEDOT NPs were synthesized via chemical oxidation polymerization in miniemulsion. The conductive PEDOT NPs were incorporated with gelatin and hyaluronic acid (HA) to create gel:HA:PEDOT-NPs scaffolds. Morphological analysis of both PEDOT NPs and scaffolds was conducted via SEM. Further characterisation included dielectric constant and permittivity variances mapped against morphological changes after crosslinking, Young’s modulus, FTIR, DLS, swelling studies, rheology, in-vitro, and in-vivo biocompatibility studies were also conducted. Results: Incorporation of PEDOT NPs increased the conductivity of scaffolds to 8.3 × 10–4 ± 8.1 × 10–5 S/cm. The compressive modulus of the scaffold was tailored to match the native spinal cord at 1.2 ± 0.2 MPa, along with controlled porosity. Rheological studies of the hydrogel showed excellent 3D shear-thinning printing capabilities and shape fidelity post-printing. In-vitro studies showed the scaffolds are cytocompatible and an in-vivo assessment in a rat SCI lesion model shows glial fibrillary acidic protein (GFAP) upregulation not directly in contact with the lesion/implantation site, with diminished astrocyte reactivity. Decreased levels of macrophage and microglia reactivity at the implant site is also observed. This positively influences the re-establishment of signals and initiation of healing mechanisms. Observation of axon migration towards the scaffold can be attributed to immunomodulatory properties of HA in the scaffold caused by a controlled inflammatory response. HA limits astrocyte activation through its CD44 receptors and therefore limits scar formation. This allows for a superior axonal migration and growth towards the targeted implantation site through the provision of a stimulating microenvironment for regeneration. Conclusions: Based on these results, the incorporation of PEDOT NPs into Gel:HA biomaterial scaffolds enhances not only the conductive capabilities of the material, but also the provision of a healing environment around lesions in SCI. Hence, gel:HA:PEDOT-NPs scaffolds are a promising TE option for stimulating regeneration for SCI.